A Novel Tyrosinase Gene Plays a Potential Role in Modification the Shell Organic Matrix of the Triangle Mussel Hyriopsis cumingii - Ren, Gang (Front Physiol, 2020)
Although tyrosinases have been speculated to participate in the shell formation of mollusks, there is still a lack of experimental evidence to support this assumption. In this study, a novel tyrosinase designated HcTyr2 was isolated and characterized from the freshwater mussel Hyriopsis cumingii. The change in HcTyr2 mRNA expression during the process of embryonic development was detected by real-time quantitative PCR. The result showed that the expression of HcTyr2 mRNA was significantly upregulated at the stages of gastrulae and unmatured glochidia (P < 0.05), suggesting that this gene might fundamentally participate in the biogenesis and growth of the initial shell. Meanwhile, the upregulation of HcTyr2 mRNA at the stages of shell regeneration 24 h and 9 days after shell notching in the mantle edge (P < 0.05) implied that it might play an important role in shell periostracum and nacre formation by mediating the cross-linking of quinoproteins to promote the maturity of organic matrix. Additionally, the knockdown of HcTyr2 mRNA by RNA interference resulted in not only the suppression of periostracum growth but also structural disorder of nacre aragonite tablets, as detected by scanning electron microscopy. These results suggested that HcTyr2 might regulate the growth of shell by its oxidative ability to transform soluble matrix proteins into insoluble matrix proteins, then promoting the maturity of the shell organic framework in H. cumingii. In general, our results suggested the importance of HcTyr2 in the shell formation and regeneration of H. cumingii.